ANALISIS KAIDAH-KAIDAH FIQIH MUAMALAH DAN IMPLEMENTASINYA DI INDONESIA (STUDI KITAB AL-ASYBAH WA AN-NADZHAIR AL-SUYUTHI) - Abdul Rahem Habel; Misno; Ahmad Waki (JURNAL ALAMIAH, 2022)
The purpose of this research is to examine and analyze the principles of muamalah fiqh contained in the book al-Asybah wa an-Nadhair written by Imam Jalaluddin al-Suyuthi and its implementation in Indonesia. This type of research is library research, the data used is qualitative data obtained from book study (book study) for 2 years, especially on muamalah fiqh principles. The method used in this thesis is descriptive-analytic-implementative, namely determining, describing, and classifying objectively the data being studied as well as interpreting the data, then the data that has been analyzed is compared to find common ground.The result of this study is that al-Suyuthi's istinbath method in exploring fiqh law, namely not only referring to the Al-Qur'an and as-Sunnah as the main source, but al-Suyuthi also uses a comparative approach to schools of thought (Hanafiyyah, Malikiyyah, Shafi' iyyah and Hanabilah) which of course cannot be doubted whose validity is quite comprehensive, so that it can give birth to fiqh principles that can be accepted among Muslim communities in general throughout the world, and even in Indonesia, some of his fiqh rules have been made as products of fiqh law which valid. Meanwhile, the correlation of al-Suyuthi's fiqh law to contemporary muamalah practices in Indonesia is still very relevant. Because among the 137 DSN-MUI fatwas (Fatwa 137/DSN-MUI/IX/2020) use 30% of al-Suyuthi's fiqh rules.